Description of Panagrolaimus namibiensis n. sp. (Rhabditida: Panagrolaimidae), an Anhydrobiotic Nematode from the Namib Desert of Namibia - Rawson Christopher J.; Nemmers London; Criswell Stacey; Smythe Ashleigh B.; Burke Alison K.; Marais Eugene; Maggs-Kölling Gillian; Treonis Amy M. (Journal of Nematology)
Panagrolaimus namibiensis n. sp. was recovered and cultured from soils collected under Arthraerua leubnitziae (pencil-bush) in the Namib Desert of Namibia, one of the driest terrestrial habitats on Earth. It is described here based on morphometrics, scanning electron micrographs, light images, line drawings, and molecular data. The new species is distinguished by having a conspicuous posterior deirid, a hook-shaped stegostomal dorsal tooth, and anterior deirids and excretory pore aligned at mid-bulb. It was morphologically compared to eleven well-described species in the genus with which it shared similar labial structure (six distinct rounded lips, and low lip segments separated in pairs), conoid tail, and/or a lateral field with three incisures, including P. labiatus, P. kolymaensis, P. davidi, P. rigidus, and P. superbus. Bayesian phylogenetic analyses using SSU and LSU rDNA each placed P. namibiensis n. sp. within clades of Panagrolaimus species, although the two trees resolved its relationship to previously described species differently. Furthermore, our analyses showed the genus is not monophyletic. In a laboratory experiment, P. namibiensis n. sp. survived exposure to 0% relative humidity for 24 h, demonstrating the anhydrobiotic ability of this species that contributes to its survival in the Namib Desert.